Influence of Busy Book Media on Learning Outcomes of Students with Intellectual Disabilities in Addition Operation - Ria Frestika Sari; Purna Bayu Nugroho (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematics learning for students with intellectual disabilities needs to be designed in a simple and easy-to-understand manner, especially on basic materials such as addition operations. However, the learning outcomes of students with intellectual disabilities at Sukamaju Special Needs School (SLBN) on addition operations are still below the Minimum Completion Criteria (MCC), so appropriate learning media are needed to improve student understanding. One of the media that can be used is Busy Book. The study was intended to see whether there is an effect of using Busy Book media on the learning outcomes of students with intellectual disabilities in addition operations at Sukamaju Special Needs School (SLBN). The research method used was a pre-experimental with a one-group pretest-posttest design. The population of this study was all students with intellectual disabilities at Sukamaju Special Needs School (SLBN) in the 2025/2026 academic year. The research sample was determined using a cluster random sampling technique, so that grade 10 students were selected as the research sample. The research instrument was an essay test on addition operations, which had been tested for validity and reliability before being used. The t-test results showed a calculated t value of 6.555 and a calculated t table of 1.8596, which means that the calculated t value is greater than the t table. The results of the study indicate that the Busy Book media influences the learning outcomes of mentally retarded students on the addition arithmetic operation material. This finding indicates that the manipulative and visual Busy Book media is an effective alternative learning media to help students with mental retardation understand basic mathematical concepts.